Związek metropolitalny jako organizator publicznego transportu zbiorowego - Mielczarek-Mikołajów, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Tadeusz Bigo is presented in literature primarily as the author of the theory of local self-government and the concept of public-legal relationships. Therefore, the question arises whether the structures of a public-law union can be helpful in examining other legal structures, e.g. a metropolitan union. Currently, there is a dispute in Poland over the legal nature of the metropolitan union. The only example of the functioning of such an entity in our country is the metropolitan association of the Silesian Voivodeship. The analysis made in this article will mainly concern the performance of tasks in the field of collective public transport in the Silesian metropolis.
Keywords: Tadeusz Bigo; metropolitan union; collective public transport